The Bacterial Flora and their Possible Association with Spoilage in a Variety of Fresh- Water Fish: Cyprinus carpio. var. communis - SEN, RANJIT; PAL, R. N.; GOPALAKRISHNAN, V. (Fishery Technology, 1966)
The bacteria from a variety of fresh - water fish, Cyprinus carpio. var. communis, showed the presence of micrococci, Gram positive and Gram negative rods. These have been characterised as far as was possible. Of thirty-eight strains of bacteria used, only six strains were considered as causing spoilage of fish flesh in experiments where flesh was incubated with individual cultures of the bacteria. These six strains had been found on the surface and/or intestine of the fish and supports the suggestions that, after death, invasion of flesh by bacteria from the surface and intestine could be the cause of bacterial spoilage of fish.